50 Years of Emmonsia Disease in Humans: The Dramatic Emergence of a Cluster of Novel Fungal Pathogens (2015)
ABSTRACT: New species of Emmonsia-like fungi, with phylogenetic and clinical similarities to Blastomyces and Histoplasma, have emerged as causes of systemic human mycoses worldwide. They differ from classical Emmonsia species by producing a thermally-dependent, yeast-like phase rather than adiaspores, and by causing disseminated infections, predominantly in immunocompromised patients and often with high case-fatality rates. Such differences will be important for clinicians to consider in diagnosis and patient management, and for microbiologists who may encounter these fungi with increasing frequency. (Tomado de la introducción del artículo)